Google Translate in Academic Writing Class: How EFL Learners Use and Perceive It - Ariyanto, Tesya Savera; Setiamunadi, Antonina Anggraini (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study is to investigate the perspectives of tertiary level Academic Writing students towards the use of GT in their Academic Writing class; whether they think it is helpful in assisting them in the learning process or not. The researchers attempted to answer the research question of “What are the learners’ perceptions towards the use of GT as a learning support in Academic Writing class?” because there are still very few studies that have examined the use of GT as a learning support tool in Academic Writing class. The study uses a qualitative approach through the use of interviews as a data collection instrument. The interviews were conducted with five participants from the English Language Education program of the Faculty of Language and Arts in one private university in Central Java. The participants are five students who had taken their Academic Writing class in the previous semester before the research was conducted. The findings of the study show that all participants agree that GT is helpful for them in reading and writing journal articles, and also helps them to expand their vocabulary. However, they perceive that they rely heavily on GT to help them finishing their writing assignments. Besides that, they perceive GT as not helping them become more proficient with English grammar. HIGHLIGHTS: Students perceived Google Translate to be helpful for them in reading and writing journal articles, and by using Google Translate to help them reading and writing journal articles, their vocabulary knowledge also expands. However, the students also perceived that they had a big dependency on the use of Google Translate in helping them doing the reading and writing tasks in Academic Writing class. Another drawback from using Google Translate in their Academic Writing class is that they perceived it as not helping them become more proficient with English grammar.